(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research expounds the computer aided design application in modern fashion design teaching present situation, and ordering in teachers working task, based on the typical types of clothing products to enterprises as the teaching content of the carrier, the enterprise real tasks in classroom teaching method, attach importance to students learning and the consistency of the practical work, takes student’s practical teaching, explore the classroom and the requirements of the enterprise integration technology Innovative.